A critical discourse analysis of ELT institutional contradictions in language policy and recruitment in Japan - Simon James Perry (Universitas Syiah Kuala, 2023)
This paper analyses a series of websites of language institutions in Japan and highlights the consistent contradictions between the language policies advertised and the recruitment of non-native English-speaking teachers (NNESTs) conducted. I did a qualitative website study that involved an analysis of the most in-demand ELT companies and organizations in Japan. The websites were of ELT institutions, which were a mix of private institutions that teach for profit, and organisations that are mediators in supplying teachers (Assistant Language Teachers-ALTs) for schools around the country. The aim of this was to compare and contrast the discourse in language ideology with recruitment policies at these companies regarding NNESTs. Conducting a study of these companies' websites enabled me to find and highlight trends in recruitment and language ideologies where I found a series of inconsistencies but also some encouraging trends in moves towards a more global outlook in teacher recruitment and discourse ideology. At the heart of the analysis was the question of whether a move towards more NNEST recruitment was due to changes in language ideology or economic necessity. The increase in non-native English-speaking teacher recruitment in Japan would be an encouraging development in attitudes and policy if it was related to a recognition of how the linguistic landscape in the 21st century is evolving but it seems apparent that economic factors are the motivating factor.